Hydrogen breath test in patients with severe constipation: the interference of the mixing of intestinal content. Issue 12 (December 2014) - Di Stefano, M.; Mengoli, C.; Bergonzi, M.; Miceli, E.; Pagani, E.; Corazza, G. R.
Abstract Background The diagnostic accuracy of the hydrogen (H2) breath test might be reduced by the release of preformed H2, trapped in hard stools. Test solution ingestion might induce the mixing of colonic content and a false positive result. We studied severely constipated patients, at diagnosis and after the normalization of bowel function, to clarify whether this mechanism affects test results. Methods Twenty functional constipated patients, 10 consecutive patients with functional diarrhea and 10 healthy volunteers underwent (i) a H2 breath test after lactulose, to exclude differences among the groups in fermenting capacity; (ii) breath H2 excretion monitoring after non‐absorbable, non‐fermentable PEG‐electrolyte solution, to exclude the role of the delivery to the colon of preexisting fermentable substrates or of the release of preformed H2 entrapped in the feces; (iii) H2 measurement during a 7‐h fasting period, to exclude the role of spontaneous variations of breath gas excretion; and (iv) breath H2 excretion monitoring after PEG, after normalization of bowel function. Key Results All the subjects excreted similar amounts of H2 after lactulose. After PEG, only severely constipated patients showed significant breath H2 excretion, theoretically able to induce a false positivity of the lactose breath test in 70% of patients and a false positivity of glucose breath tests in 50% of patients. Breath H2 excretion after PEG disappeared if fecal consistency improved after therapy. Conclusions & Inferences Severely constipated patients may harbor preformed gas in hard stools which can be released when mixing of the intestinal content is induced. This mechanism may interfere with breath test results.